Relationship of demoralization with anxiety, depression, and quality of life: A Southern European study of Italian and Portuguese cancer patients. Issue 11 (6th August 2018) - Nanni, Maria Giulia; Caruso, Rosangela; Travado, Luzia; Ventura, Cidalia; Palma, Alessandra; Berardi, Alejandra M.; Meggiolaro, Elena; Ruffilli, Federica; Martins, Cristina; Kissane, David; Grassi, Luigi
Abstract: Background: Demoralization syndrome is a significant condition that has not been greatly studied in Southern European countries. Aims: To extend the knowledge of demoralization in Southern Europe by examining its prevalence according to different methods of assessment, its relationship with anxiety and depression, and its impact on quality of life (QoL) among cancer patients. Methods: A convenience sample of 195 cancer outpatients from two oncology centers (102 from Lisbon, Portugal, and 93 from Ferrara, Italy) participated in an observational, cross‐sectional study using the Diagnostic Criteria of Psychosomatic Research‐Demoralization interview (DCPR/D) and psychometric tools (Demoralization scale‐DS; Patient Health Questionnaire–9/PHQ‐9; Hospital Anxiety Depression Scale‐HADS; and European Quality of Life‐5‐EQ‐5D). Results: A 25.1% prevalence (CI 95%, 0.19‐0.31) of clinically relevant demoralization was reported on the DCPR/D interview. A total demoralization score cutoff score ≥ 25 maximized sensitivity (81.6%), and specificity (72.6%) in identifying DCPR/D demoralized patients. The DCPR/D and DS were associated with poorer levels of QoL. About half of the patients who were demoralized were not clinically depressed (PHQ‐9). Self‐reported suicidal ideation (PHQ‐9 item 9) was found in a minority of patients (8.2%), most of whom (77%) were cases of depression (PHQ‐9), but one‐quarter (23%) were not depressed, yet moderately/severely demoralized (DCPR/D and DS). Conclusions: This Southern European study confirms the importance of demoralization in cancer patients as a different condition with respect to depression and its relationship with poor QoL and suicidal ideation.